2017
DOI: 10.1002/ajhb.23034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of baseline frequency of sister chromatid exchanges in an Italian population according to age, sex, smoking habits, and gene polymorphisms

Abstract: We describe the association between some phase I, phase II, and DNA-repair gene polymorphisms with increased SCEs frequencies, reinforcing the importance of genetic analysis in biomonitoring studies. Sex and age were found to be important endogenous factors that affect the level of genomic damage and the replicative capacity of cells, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
2
6
1
Order By: Relevance
“…Therefore, analyzing the percentage of HFC, as a "measure of SCE rate" may be more sensitive than the mean of SCE to detect effects due to chemical exposure, such as smoking, when an effect is not clearly detected by differences in mean SCE value (95). Our results concerning the influence of gender agree with published studies showing no association with the SCE frequency (87,92,96), although positive findings were also reported showing that women display a higher frequency of SCE comparatively to men (85). Also, no influence of age was observed in agreement with recent studies (85,92).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, analyzing the percentage of HFC, as a "measure of SCE rate" may be more sensitive than the mean of SCE to detect effects due to chemical exposure, such as smoking, when an effect is not clearly detected by differences in mean SCE value (95). Our results concerning the influence of gender agree with published studies showing no association with the SCE frequency (87,92,96), although positive findings were also reported showing that women display a higher frequency of SCE comparatively to men (85). Also, no influence of age was observed in agreement with recent studies (85,92).…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, in children, ETS exposure was associated with increased SCE (27). On the other hand, it is recognized that the measurement of SCEs in PBLs is a sensitive biomarker of exposure to cigarette smoke (32,33,(85)(86)(87)(88)(89)(90)(91)(92). The cigarette smoke effect was not observed in our study, mainly constituted by light smokers (amount of daily cigarette consumption: 16.47 ± 7.25; range 3-30).…”
Section: Discussioncontrasting
confidence: 69%
“…CYP2C19*2 results from a guanine (G) to adenine (A) transition at position 681 in exon 5, producing an aberrant splicing site and encoding enzymes with decreased activity 42 . This polymorphism was related to genotoxicity in a previous study of Santovito et al, where CYP2C19 A/A subjects turned out to show a frequency of sister chromatid exchanges (SCEs) significantly higher with respect to the CYP2C19 G/G homozygote genotypes 43 .…”
Section: Discussionmentioning
confidence: 85%
“…While some reports showed no effect of these polymorphisms in modulating the level of genomic damage 12 , 34 , 45 , 46 , others found a significant association. As example, Santovito et al 43 observed higher frequencies of SCEs, CAs, and Ab.C among pathologists with GSTT1 -null genotypes than in the reference group. Several other epidemiological studies evaluating exposure to organic solvents, reported the GSTM1 -null genotype associated with an increase in cytogenetic biomarkers, probably due to the absence of detoxification activity that may affect the amount of DNA damage 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous in vivo studies involving a larger number of subjects, the results related to a possible role of sex in determining the level of genomic damage were conflicting. Indeed, a positive association between the frequencies of CAs, sister chromatid exchanges and sex was found by our group in two control populations (n = 101 and n = 230, respectively), with females showing higher levels of genomic damage (Santovito et al, 2017), whereas in another study this association was not observed (Santovito et al, 2016) Finally, the CBPI value was decreased with CHT treatments. However, this reduction was not statistically significant, indicating that CHT does not seem to produce significant effects on the proliferation/mitotic index when its concentration is equal or less than 0.020 µg/mL.…”
Section: 2 Effect Of Cht On Mns Formationmentioning
confidence: 49%